ORGANIZATIONAL CULTURAL HARMONY: THE KEY TO IMPROVING EMPLOYEE PERFORMANCE - Ismaila Tompo; Bahri Majid (Entrepreneurship Undergraduate Program at Amkop Business School, 2023)
This study examines the importance of harmonization of organizational culture on employee performance in car AC workshops. The auto air conditioning industry has unique characteristics that influence the way organizational culture is implemented and the performance of employees within it. We analyze the obstacles often encountered in achieving harmonization of organizational culture, including differences in technical skills, time pressures, effective communication, employee development, and adaptation to technological change. This study concludes that harmonization of organizational culture with employee performance is very important in car air conditioning workshops. An organizational culture that supports values such as safety, quality, teamwork, and employee development can increase employee motivation and productivity. Effective communication, management support, and recognition of employee contributions also play an important role in achieving harmonization. In the context of this competitive industry, harmonization of organizational culture is a key factor for achieving long-term excellence and success. This research provides insight into how the car air conditioning workshop industry can overcome the obstacles faced to achieve harmonization of positive organizational culture and superior performance. Keywords: Harmonization, Organizational Culture, Employee Performance